Evolution of grain size distributions and bed mobility during hydrographs in gravel‐bed braided rivers. Issue 1 (14th October 2018) - Peirce, S.; Ashmore, P.; Leduc, P.
Abstract: Evolution of bed material mobility and bedload grain size distributions under a range of discharges is rarely observed in braiding gravel‐bed rivers. Yet, the changing of bedload grain size distributions with discharge is expected to be different from laterally‐stable, threshold, channels on which most gravel bedload theory and observation are based. Here, simultaneous observations of flow, bedload transport rate, and morphological change were made in a physical model of a gravel‐bed braided river to document the evolution of grain size distributions and bed mobility over three experimental event hydrographs. Bedload transport rate and grain size distributions were measured from bedload samples collected in sediment baskets. Morphological change was mapped with high‐resolution ( 1 mm precision) digital elevation models generated from close‐range digital photogrammetry. Bedload transport rates were extremely low below a discharge equivalent to 50% of the channel‐forming discharge (dimensionless stream power 70). Fractional transport rates and plots of grain size distributions indicate that the bed experienced partial mobility at low discharge when the coarsest grains on the bed were immobile, weak selective mobility at higher discharge, and occasionally near‐equal mobility at peak channel‐forming discharge. The transition to selective mobility and increased bedload transport rates coincided with the lower threshold for morphological change measured by the morphological active depth and active width. Below this threshold discharge, active depths were of the order of D90 and active widths were narrow (< 3% of wetted width). Above this discharge, both increased so that at channel‐forming discharge, the active depth had a local maximum of 9D90 while active width was up to 20% of wetted width. The modelled rivers approached equal mobility when rates of morphological change were greatest. Therefore, changes in the morphological active layer with discharge are directly connected to the conditions of bed mobility, and strongly correlated with bedload transport rate. © 2018 John Wiley & Sons, Ltd. Abstract : Investigation in a physical model of gravel‐bed braided river indicated that bed mobility transitioned from partial mobility to selective mobility at discharges 50% of peak discharge, and approached equal mobility at the highest (i.e., diurnal peak/channel‐forming) discharges. The threshold between partial mobility and selective mobility coincided with a threshold for detectable morphological change and substantial increases in bedload transport rates.